2021
DOI: 10.33774/chemrxiv-2021-t8p0f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lewis Acid-Promoted Oxidative Addition at a [Ni0(diphosphine)2] Complex: The Critical Role of a Secondary Coordination Sphere

Abstract: Oxidative addition represents a critical elementary step in myriad catalytic transformations. Here, the importance of thoughtful ligand design cannot be overstated. In this work, we report the intermolecular activation of iodobenzene (PhI) at a coordinatively saturated 18-electron [Ni 0 (diphosphine)2] complex bearing a Lewis acidic secondary coordination sphere. Whereas alkyl-substituted diphosphine complexes of Group 10 are known to be unreactive in such reactions, we show that [Ni 0 (P2B Cy 4)2] (P2B Cy 4 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…12 A role for SCS boron groups was demonstrated using the nickel(0) compound, [Ni 0 (P2B Cy 4)2] -a bis(diphosphine) compound that promotes the oxidative addition of iodoarenes (ArI) to give [Ni II (P2B Cy 4)(Ar)(I)] (Chart 1A). 13 By contrast, and consistent with previous literature precedent, the n-propyl derivative, [Ni(dnppe)2] (dnppe = 1,2-bis(di-n-propylphosphino)ethane) displayed no such reactivity, pointing to an important role for P2B Cy 4 as a labile ligand precursor. These initial studies concerned tetra-substituted variants owing to ease in synthesis of the tetrakisallylphosphinoethane (tape) precursor, obtained by reaction of 1,2-bis(dichlorophosphino)ethane with excess allyl magnesium chloride.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…12 A role for SCS boron groups was demonstrated using the nickel(0) compound, [Ni 0 (P2B Cy 4)2] -a bis(diphosphine) compound that promotes the oxidative addition of iodoarenes (ArI) to give [Ni II (P2B Cy 4)(Ar)(I)] (Chart 1A). 13 By contrast, and consistent with previous literature precedent, the n-propyl derivative, [Ni(dnppe)2] (dnppe = 1,2-bis(di-n-propylphosphino)ethane) displayed no such reactivity, pointing to an important role for P2B Cy 4 as a labile ligand precursor. These initial studies concerned tetra-substituted variants owing to ease in synthesis of the tetrakisallylphosphinoethane (tape) precursor, obtained by reaction of 1,2-bis(dichlorophosphino)ethane with excess allyl magnesium chloride.…”
Section: Introductionsupporting
confidence: 84%
“…1 H NMR spectra are reported in parts per million (ppm) and are referenced to residual solvent e.g., 1 H(C6D6): δ 7.16; 13 C(C6D6): 128.06; coupling constants are reported in Hz. 13 C, 11 B, and 31 P NMR spectra were performed as proton-decoupled experiments and are reported in ppm.…”
Section: Experimental Datamentioning
confidence: 99%
“…Recent work in our laboratory has concentrated on the preparation of diphosphine ligands having ligands featuring borane groups in the secondary coordination sphere (SCS) (Chart 1B). 17,18,19,20 We and others have shown that these groups are participatory in chemical transformations, offering stabilization to Lewis basic substrates such as amides, sulfides, hydroxides, alkyl anions, hydrides, pyridines, and more. 21 With the aim of expanding the 'diphosphine ligand toolbox' our initial reports focused on symmetrical diphosphine compounds with four 20 or two 22 boranes.…”
mentioning
confidence: 99%
“…A cluster of other allyl signals from 5.14 > dH > 4.90 ppm were also observed for the remaining C(sp 2 )H protons. 8,13,17 "All-alkyl" analogues 2 and 4 using dnppe (dnppe = 1,2-bis(di-n-propylphosphino)ethane) were also synthesized following similar procedures to that of 1 and 3 (Scheme 1). Single-crystal X-ray diffraction (scXRD) was used to confirm and structurally authenticate the identities of compounds 2, 3, and 4.…”
Section: Synthesis Of {[Fe]-cl} Complexesmentioning
confidence: 99%
“…[5][6][7] Furthermore, a role for such Lewis acidic SCSs has been exposed in iodoarene C-I bond oxidative addition using a [Ni(diphosphine)2] complex, and in producing divergent reaction pathways in the reaction of Ni(0) with organoazides. 8,9 Our group has contributed a number of diphosphine ligands where unsaturated R-groups serve as modifiable sites for the installation of Lewis-acids (boranes; -BR2) via hydroboration. 10,11,12,13 In most cases, installation is performed post-coordination, the success of which depends on the nature of metal starting material.…”
Section: Introductionmentioning
confidence: 99%